Green Tourism - Ali Hasan (Media Wisata, 2014)
Green tourism is defined as environmentally friendly tourism activities with various focuses and meanings. In a broad term, green tourism is about being an environmentally friendly tourist or providing environmentally-friendly tourist services. The green tourism concept would be highly appealing to tourism enterprises and operators owing to increasing governmental pressure to improve environmental performance by adopting effective and tangible environmental management techniques. Green tourism is a form of tourism involving visiting fragile, pristine, and relatively undisturbed natural areas, intended as a low-impact and often small scale alternative to standard commercial tourism. Its purpose may be to educate the traveller, to provide funds for ecological conservation, to directly benefit the economic development and political empowerment of local communities, or to foster respect for different cultures and for human rights. Green Tourism has been considered a critical endeavour by environmentalists, so that future generations may experience destinations relatively untouched by human intervention. Furthermore, the achievement and promotion of internationally recognized environmental awards would be instrumental to the tourism enterprises in marketing their services. As a result, many concerned and responsible parties put forward recommendations for green tourism products to regulate tourism’s negative impacts. This conceptual paper attempts to discuss the green tourism concept its processes as well as explain approaches of green tourism industry can legitimately open up new areas for the more discriminating and wider range of the market, and tourists or visitors can enjoy the holiday they want with a clear conscience. Responsible green tourism programs and plans include those that minimize the negative aspects of conventional tourism on the environment and enhance the cultural integrity of local people. Therefore, in addition to evaluating environmental, social and cultural factors, an integral part of green tourism is the promotion of recycling, energy efficiency, water conservation, and the creation of economic opportunities for local communities. For these reasons, green tourism often appeals to advocates of environmental and social responsibility. Marketing people -all in public, government and private level specialists- working in the tourism sector, should configure the best green solutions for the current and future strategies. The real green alternatives are needed to suggest a new perspective(re-thinking process) about tourism marketing strategies.